PENGARUH DIMENSI MANAJEMEN PENGETAHUAN TERHADAP KINERJA POLISI (Studi pada Anggota Kepolisian Negara Republik Indonesia Resor Kabupaten Muna) - Eka Kurniawan Muntu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study was to examine the influence of the dimensions of knowledge management on the performance of police officers at Muna Police. This type of research was a survey with a cross sectional study design. The population in this study were 221 police officers at the Muna Police Station, Southeast Sulawesi Province. Determination of the sample in this study using  simple random sampling technique in order to obtain a number of 67 people. The results showed that There is an effect of knowledge acquisition/acquisition on the performance of members of the Muna Police Resort, there is an effect of sharing knowledge on the performance of members of the Muna Regional Police, there is an effect of the use of knowledge on the performance of members of the Muna Police, there is no effect of documentation/store of knowledge on the performance of members of the Muna Police. there is an effect of knowledge protection on the performance of members of the Muna Police Police. And collectively the use of knowledge is the most influential variable on the performance of members of the Muna Police Police.